2023
DOI: 10.3389/fenvs.2023.1137496
|View full text |Cite
|
Sign up to set email alerts
|

Soil and groundwater contamination by crude oil spillage: A review and implications for remediation projects in Nigeria

Abstract: Management of soil and groundwater resources has been recognized as essential to meeting the sustainable development goals of Agenda 2063 of the African Union. As Africa’s fastest growing population with over 200 million people, Nigeria is responsible for leading the continent’s environmental sustainability goal. Nigeria has seen a sizable number of crude oil spillages that have contaminated its soils and groundwater resources, and several of these contaminated sites are to be cleaned up yet. There needs to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 138 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…The primary focus of some environmental protection research has been the ecological behavior of rock and oil pollutants in soil [1,2]. The presence of large quantities of oil within the soil environment had a profound impact on its characteristics [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The primary focus of some environmental protection research has been the ecological behavior of rock and oil pollutants in soil [1,2]. The presence of large quantities of oil within the soil environment had a profound impact on its characteristics [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of petroleum products in global economy has resulted in continuous distribution of large amounts of crude oil all over the world, which has led to pollution of the environment. Generally, crude oil gains access into the environment through leak of oil tankers, cleaning of tankers by merchants, leaks during exploration, refining, storage and transportation [2]. There are also small-scale releases, which at times may pass unnoticed, particularly in developing countries like Nigeria [3].…”
Section: Introductionmentioning
confidence: 99%
“…These levels are significantly higher than the U.S. Environmental Protection Agency (EPA)'s maximum permissible levels of 5 µg/L, 1 mg/L, and 700 µg/L, respectively [11]. As an example of petrogenic environmental water contamination, Adeniran et al provided a comprehensive review of groundwater contamination by crude oil spillages [12]. On the other hand, in addition to the fact that BTEX compounds enter the environment through the sources referred to above, other sources include industrial activities, and BTEXs have been found to be common groundwater contaminants at 1 to 3 µg/L [13].…”
Section: Introductionmentioning
confidence: 99%